Occurrence and Origins of Cerium Dioxide and Titanium Dioxide Nanoparticles in the Loire River (France) by Single Particle ICP-MS and FEG-SEM Imaging - Phalyvong, Karine; Sivry, Yann; Pauwels, Hélène; Gélabert, Alexandre; Tharaud, Mickaël; Wille, Guillaume; Bourrat, Xavier; Benedetti, Marc F. (Frontiers in Environmental Science, 2020)
The need to quantify engineered nanoparticles (ENPs) in the environment is due to the increasing incorporation of these particles in the daily products, which threatens human health and can possibly impact natural systems. Ceria NPs (CeO2NPs) and titanium dioxide NPs (TiO2NPs) are two of the most used ENPs in the world. In this study their occurrence was determined in river waters with accurate and relevant techniques such as single particle ICP-MS (spICPMS). In the Loire River (France), the variation of both CeO2NPs and TiO2NPs could be assessed locally, with an increase of the concentrations near a wastewater treatment plant (WWTP) outlet as well as in a lake connected to the river and dedicated to outdoor activities. In the upstream river water, supposedly less impacted by NPs, 6.4 ± 1.2 × 104 part mL–1 Ce-bearing and 13.4 ± 1.8 × 104 part mL–1 Ti-bearing particles were measured. These values increased to 33.9 ± 3.4 × 104 part mL–1 Ce-bearing and 80.3 ± 3.4 × 104 part mL–1 Ti-bearing particles near the WWTP outlet. Equivalent size for sphere distributions ranged from 24 nm to 70 nm for CeO2 and from 80 nm to 500 nm for TiO2 in the river water. In the lake, a raise of the concentrations has been observed with 38.3 ± 2.0 × 104 part mL–1 and 71.6 ± 2.1 × 104 part mL–1 containing Ce and Ti, respectively, with similar size distributions. FEG-SEM imaging confirms the occurrence of Ce- and Ti-bearing particles in the water samples. On the contrary, NPs seem to undergo strong heteroaggregation in the Loire river water. The Ce/La elemental ratios does not evolve from upstream to downstream the WWTP outlet, suggesting that a natural origin cannot be excluded to explain the increase observed in NPs number concentration. On the contrary, the Ce/La ratio increases in the outdoor activities center, which suggests the contribution of NPs potentially related to the cars parked nearby. Besides, elemental ratios Ti/V and Ti/Y have been assessed to highlight an anthropogenic source of Ti in both sampling sites, possibly to the sunscreens used during the summer.